Feasibility, safety, and efficacy of aerobic training in pretreated patients with metastatic breast cancer: A randomized controlled trial. Issue 12 (6th April 2018) - Scott, Jessica M.; Iyengar, Neil M.; Nilsen, Tormod S.; Michalski, Meghan; Thomas, Samantha M.; Herndon, James; Sasso, John; Yu, Anthony; Chandarlapaty, Sarat; Dang, Chau T.; Comen, Elizabeth A.; Dickler, Maura N.; et al.
Abstract : BACKGROUND: The investigation of exercise training in metastatic breast cancer has received minimal attention. This study determined the feasibility and safety of aerobic training in metastatic breast cancer. METHODS: Sixty‐five women (age, 21‐80 years) with metastatic (stage IV) breast cancer (57% were receiving chemotherapy, and >40% had ≥ 2 lines of prior therapy) were allocated to an aerobic training group (n = 33) or a stretching group (n = 32). Aerobic training consisted of 36 supervised treadmill walking sessions delivered thrice weekly between 55% and 80% of peak oxygen consumption (VO2peak ) for 12 consecutive weeks. Stretching was matched to aerobic training with respect to location, frequency, duration, and intervention length. The primary endpoint was aerobic training feasibility, which was a priori defined as the lost to follow‐up (LTF) rate (<20%) and attendance (≥70%). Secondary endpoints were safety, objective outcomes (VO2peak and functional capacity), and patient‐reported outcomes (PROs; quality of life). RESULTS: One of the 33 patients (3%) receiving aerobic training was LTF, whereas the mean attendance rate was 63% ± 30%. The rates of permanent discontinuation and dose modification were 27% and 49%, respectively. Intention‐to‐treat analyses indicated improvements in PROs, which favored the attention control group ( P values > .05). Per protocol analyses indicated that 14 of 33 patients (42%) receiving aerobic training had acceptable tolerability (relative dose intensity ≥ 70%), and this led to improvements in VO2peak and functional capacity ( P values < .05). CONCLUSIONS: Aerobic training at the dose and schedule tested is safe but not feasible for a significant proportion of patients with metastatic breast cancer. The acceptable feasibility and promising benefit for select patients warrant further evaluation in a dose‐finding phase 1/2 study. Cancer 2018;124:2552‐60. © 2018 American Cancer Society . Abstract : The tolerability and safety of 36 supervised treadmill walking sessions delivered thrice weekly between 55% and 80% of peak oxygen consumption for 12 consecutive weeks have been investigated in 65 patients with metastatic breast cancer. Aerobic training at the dose and schedule tested is safe but is not tolerated by a significant proportion of patients with metastatic breast cancer; the acceptable tolerability and promising benefit for select patients warrant further evaluation in a dose‐finding phase 1/2 study.